Hubungan Tingkat Pengetahuan, Sikap dan Stres dengan Kejadian Hipertensi di Poliklinik RS Graha Husada Bandar Lampung - Diah Ajeng Paramita; Eko Wardoyo; Hana Zumaedza Ulfa; Giri Susanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
In controlling blood pressure, there are important factors, namely the level of knowledge, attitude and stress. This is influential because knowledge and attitude in changing a healthy lifestyle, while stress can affect blood pressure in people with hypertension. This study aims to determine the relationship between the level of knowledge, attitude, and stress with the incidence of hypertension at the Graha Husada Hospital Polyclinic, Bandar Lampung. The type of quantitative research, Analytical Survey design with Cross Sectional design. The population was 120 respondents and a sample of 55 respondents who were controlled at the Graha Husada Hospital Polyclinic, carried out in September-October 2024 with the Accidental sampling technique. Data were analyzed using the Gamma Test. The results of the study showed a relationship between the level of knowledge and the incidence of hypertension at the Graha Husada Hospital Polyclinic, Bandar Lampung with a p-value <0.001 <(0.05). The relationship between attitudes and the incidence of hypertension at the Graha Husada Hospital Polyclinic, Bandar Lampung p-value 0.001 <(0.05). The relationship between stress and hypertension incidence at the Graha Husada Hospital Polyclinic Bandar Lampung p-value 0.004 < (0.05). It is expected that knowledge, attitude and stress can be controlled well in order to reduce the incidence of hypertension and the emergence of serious complications.